Time to celebrate the most disgusting video online - Paasonen Susanna (United Kingdom, 2022)
It is 10 years since 2Girls1Cup first went viral. This forum contextualizes the video within the attention economy of social media to examine whether this particular one-minute video, by now markedly stale in its novelty appeal, is relevant in terms of online pornography, social media or the field of porn studies.
KEYWORDS: 2Girls1Cup, shock video, internet memes, ‘Not Safe for Work’, attention economy